1894-95 Ala. Laws 1081 - (:unkn) unknown (My University, 1895)
Authorized the mayor and aldermen of Tuskaloosa to collect an annual tax and license, regulate, restrain, or prohibit dealers in pistols, pistol cartridges, Bowie knives, dirk knives, gun shops, or gun repair shops.
Keywords: TAX - DEALERS